Analisis Distribusi dan Analisis Peringkat Data Kemiskinan dari Tiga Sumber Data di Kabupaten Bekasi - Cahyadie, Beny; Juanda, Bambang; Fauzi, Akhmad; Kinseng, Rilus A. (Research and Development Agency Ministry of Home Affairs, 2023)
In implementing evidence-based policies, it is necessary to support poverty data that is precise, accurate, and consistent. The goal is that various assistance, such as social assistance, PKH, groceries, pre-employment, and other subsidies, will be right on target for people experiencing poverty. The diversity of poverty data sources will have implications for the inaccuracy of targeting social assistance recipients. Until now, there are still three sources of poverty data, namely the Statistics Indonesia, the Ministry of Social Affairs (Kemensos) with Integrated Data on Social Welfare (DTKS), and TNP2K, which is now under the Coordinating Ministry for Human Development and Culture (Kemenko KMK) which also releases data targeting the Acceleration of Extreme Poverty Elimination (P3KE). The purpose of this study is to analyze the distribution of poverty data and rank analysis of poverty data from three data sources in the Bekasi Regency. The analysis method used ArcGIS 10.4 software and the administrative map shapefile for the Bekasi Regency area. In the ranking analysis of poverty data from three data sources in each sub-district in Bekasi Regency, the Preference Ranking Organization Methods For Enrichment Evaluation (PROMETHEE) method was used. The results of the analysis showed that the distribution of P3KE data is 1,317,098 people spread by decile-1 to decile-4 in all sub-districts of Bekasi Regency. Statistics Indonesia data is 229,367 people spread across each sub-district, and the number of DTKS in Bekasi Regency is 1,035,402 people, with the most distribution of data in Babelan District, namely 110,867 people out of 34,009. While the best ranking of the three sources of poverty data is Central Cikarang, Pebayuran District (0.7273), North Tambun (0.6364), Cibitung and Karang Bahagia (0.4242), North Cikarang (0.3939), South Tambun (0 .3636), Sukatani (0.2121), Serang Baru (0.1515), West Cikarang (0.1212), Tarumajaya (0.0909), East Cikarang (0.0606).